2012
DOI: 10.1063/1.4733289
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of threshold voltage fluctuation in field-effect transistors by controlling individual dopant position

Abstract: To investigate the impact of only the dopant position on threshold voltage (Vth) in nanoscale field-effect transistors, we fabricated transistors with ordered dopant arrays and conventional random channel doping. Electrical measurements revealed that device performance could be enhanced by controlling the dopant position alone, despite varying dopant number according to a Poisson distribution. Furthermore, device-to-device fluctuations in Vth could be suppressed by implanting a heavier ion such as arsenic owin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…1 The phenomenon of device fluctuations becomes increasingly important. One of the most significant issues in the scaling is the threshold voltage (V th ) fluctuation induced by the process or device structure; [1][2][3][4][5][6][7][8][9][10][11] especially the discretedopant in the channel induced random dopant fluctuation (RDF), 2 which is the major source of V th fluctuation. It has been magnified by the scaling of device size (or area) because the electrical characteristics of the device become more and more sensitive to the number of dopants in the channel.…”
mentioning
confidence: 99%
“…1 The phenomenon of device fluctuations becomes increasingly important. One of the most significant issues in the scaling is the threshold voltage (V th ) fluctuation induced by the process or device structure; [1][2][3][4][5][6][7][8][9][10][11] especially the discretedopant in the channel induced random dopant fluctuation (RDF), 2 which is the major source of V th fluctuation. It has been magnified by the scaling of device size (or area) because the electrical characteristics of the device become more and more sensitive to the number of dopants in the channel.…”
mentioning
confidence: 99%
“…In this case, the domain spacing of the confined dopants was shown to be of the order of ≈100 μm with the potential to extend the process applicability into the sub‐100 nm range by using high‐resolution molds . In the limiting case, single‐ion implantation enables truly deterministic doping, in that the precise position of every implanted ion is predetermined . While this technique can potentially address the abovementioned challenge on a local scale, the energy consumption and slow throughput associated with the process makes scaling to wafer‐scale substrates cost‐prohibitive.…”
Section: Molecular Weight Composition and Domain Spacing Of The Ps‐mentioning
confidence: 99%
“…To perform this type of quantum calculations, there are three necessary parameters: modulation of the hyperfine interaction length by gate voltage, control of "on-off" states for single donor, and the resonance flipping of nuclear spins by global magnetic field. Pla et al [16] reported the readout and control of 31 P spin in Si with 99.8% fidelity. Vrijen et al [17] presented in their work that Si/Ge epitaxial heterostructures were selected to control the single-phosphorus electron spin.…”
Section: Atom Control and Devices Designmentioning
confidence: 99%
“…When the gate length of MOSFET is only ~10 nm, the active channel region of devices will only contain several dopants, and the fluctuation in dopant number will generate much stronger random telegraph noise than the average threshold voltage [29] , [30]. Ohdomari group reported the phosphorus dopant array [6], As dopant array [31], and other dopants [32] in the silicon devices. It was found that the fluctuation of dopants increases the threshold voltage variation significantly ( Figure 5), making the circuitry consisting of these transistors less reliable.…”
Section: Dendrimers -Fundamentals and Applicationsmentioning
confidence: 99%